The Effects Between Black Coffee and Mixed Coffee Consumption Towards Gastroesophageal Reflux Disease (GERD) Symptomps - Arsanti, Nabila Mayori; Dewi, Rita; Tenggara, Riki; Rensa, Agnes (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Gastroesophageal Reflux Disease (GERD) is a disease characterized by regurgitation of stomach contents into the esophagus. Signs and symptoms of GERD are regurgitation and heartburn. One of the triggers for GERD is coffee consumption.Aims: This study aims to determine differences in the effect of coffee consumption on black coffee drinkers and mixed coffee drinkers on symptoms of GERD.Methods: A cross-sectional study was conducted in Bekasi City and DKI Jakarta using a demographic questionnaire and consumption of black coffee and mixed coffee and the Gastroesophageal Reflux Disease Questionnaire (GERDQ) in Indonesian language. Data analysis used the Mann-Whitney test to test the percentage difference between the dependent variable and the independent variable.Results: This study obtained 195 participants who were analyzed. As much as 50.8% (99 people) consumed mixed coffee and 52.8% (19 people) had GERD and 50.3% (80 people) did not experience GERD. As many as 49.2% (96 people) consumed black coffee and 47.2% (17 people) had GERD and 49.7% (79 people) did not have GERD. The Mann-Whitney test did not show a significant change (Asymp. Sig. 0.790).Conclusion: There is no significant comparison between the effects of coffee consumption on black coffee drinkers and mixed coffee drinkers on GERD symptoms.Keywords: Gastroesophageal Reflux Disease, GERD, Black Coffee, Mixed Coffee